STUDENTS’ LEARNING DIFFICULTIES: A CORRELATIONAL STUDY ON THE INFLUENCE OF TEACHERS’ SOCIAL COMPETENCE - Muhammad Ja'far Abdul Aziz; Chairul Anwar; Saiful Bahri (ASIAN PUBLISHER, 2025)
This research explores the extent to which students’ self-efficacy shape their learning motivation within Islamic Religious Education (IRE) and character education at SMPN 5 Bandar Lampung. The research was driven by initial observations showing variations in students’ self-efficacy that may affect their engagement in learning. Using a quantitative correlational ex-post facto approach, information was collected from 75 seventh grade students, who were selected from a total of 414 participants using a simple random sampling technique. The instruments consisted of Likert-scale questionnaires measuring self-efficacy (12 items) and learning motivation (24 items), both validated and confirmed reliable with Cronbach’s alpha values of 0.872 and 0.894. The results clearly demonstrate that self-efficacy significantly and positively affects students’ motivation to learn. The coefficient of determination (R²) indicates that 24.4% of the variance in motivation is explained by self-efficacy, while 75.6% is influenced by other unexamined factors. Students with strong self-efficacy display greater confidence, persistence, and intrinsic drive, whereas those with low self-efficacy are more dependent and less engaged in classroom activities. The study’s originality stems from its emphasis on integrating Islamic religious education (IRE) with character education specifically within the context of junior high schools, a domain often overlooked compared to studies on science and mathematics. This study’s results offer empirical support showing that self-efficacy is a key factor influencing both students’ academic achievements and their engagement in religious and moral education. The findings emphasize the need to foster self-efficacy through supportive teaching strategies, positive feedback, and an encouraging classroom environment. These implications highlight how enhancing self-belief can foster stronger motivation and enrich educational practice.